Associations between objectively measured physical activity intensities and executive function in preschool children: a cross-sectional study - Xin Xiong; Jiawei Lai; Siming Wang; Jian Li; Xiaohui Pei; Jiayi Sun; Yaqi An; Zhenguo Wang (Frontiers in Psychiatry, 2026)
Background Executive function, including inhibitory control, working memory, and cognitive flexibility, develops rapidly during the preschool years and is central to children’s cognitive, behavioral, and social development. Physical activity is a potentially modifiable factor that may support executive function; however, evidence regarding the associations of specific physical activity intensities with individual executive function domains in preschool children remains limited and inconsistent. This cross-sectional study examined associations between objectively measured physical activity intensity and executive function in preschool children. Methods The analysis included 238 children aged 3–6 years (124 boys and 114 girls; mean age, 5.3 years) from three kindergartens in Guangzhou, China. Physical activity was measured for four consecutive days using a wrist-worn ActiGraph wGT3X-BT accelerometer. Executive function was assessed using the Go/No-Go, Flanker, 1-back, and Dimensional Change Card Sort (DCCS) tasks, which indexed response inhibition, interference control, working memory, and cognitive flexibility, respectively. Group comparisons, correlation and Mantel analyses, and multiple linear regression models adjusted for age, sex, and body mass index were used. Results Executive function performance differed across age groups in all tasks, with older children generally showing higher accuracy and shorter reaction times. Moderate-to-vigorous physical activity (MVPA), average daily MVPA, and the proportions of moderate physical activity and vigorous physical activity (VPA) also increased with age. In adjusted regression models, higher MVPA was nominally associated with shorter DCCS reaction time ( B = −1.950, 95% CI, −3.681 to −0.219; β = −0.143; p = 0.027), but this association did not remain statistically significant after false discovery rate (FDR) correction ( q = 0.108). VPA was associated with shorter Flanker reaction time before multiple-comparison correction ( p = 0.021), but the association did not remain significant after FDR correction ( q = 0.084). No consistent independent associations were observed between sedentary time, light physical activity, or other physical activity indicators and the remaining executive function outcomes. Conclusion Higher-intensity physical activity showed small, task-specific nominal associations with executive function reaction-time outcomes, but these associations were not robust after FDR correction. Exploratory moderation analysis suggested that the association between MVPA and cognitive flexibility varied according to age. Given the cross-sectional design, these findings should be interpreted as tentative, domain-specific patterns rather than robust or causal effects.